Image compression by approximation of polynomial functions their discrete cosine transform - Мельник, Р. А.; Климаш, Т. С. (Eastern-European Journal of Enterprise Technologies, 2012)
Methods and algorithms of image approximation using polynomial functions are considered. Compression and accuracy characteristics of image by discrete cosine transform are investigated